S53. DELINEATING SOCIAL COGNITION IN AUTISM AND PSYCHOSIS. (18th May 2020) - Ziermans, Tim; van Rijn, Sophie; Geurts, Hilde; De Haan, Lieuwe
Abstract: Background: Impaired social cognition represents a common feature in both the autism and psychosis spectrum, but direct comparisons are sparse and assessments typically restricted to a few tasks with limited ecological validity. The first aim of the present study was to compare the social cognitive profile of young individuals with autism spectrum disorder (ASD) or a first episode psychosis (FEP) with a group of typical comparisons (TC) on a comprehensive social cognition test battery. The second aim was to explore the relative contribution of autistic and psychotic traits to social cognitive performance across groups. Methods: In total 90 young individuals (M = 21.9 y, SD = 3.1 y, range = 16–30 y, 67% male) were recruited. Groups (31 FEP, 21 ASD, 38 TC) were matched for age and sex. Social cognition assessment included measures for static and dynamic emotion recognition & social inference / Theory of Mind, social attention (eye-tacking), empathy and alexithymia. Autistic and psychotic traits were assessed with self-report questionnaires (AQ-28 & SPQ-br). Results: Data collection is completed at the time of abstract submission and analyses are expected to be finalized in February 2020. Discussion: Pending the outcome of our analyses, we expect our results will provide a more complete and detailed picture of shared and unique aspects in the social cognitive profile of autism and psychosis. In general we hypothesize that both ASD and FEP, on a group-level, will significantly underperform compared to TC, but that the respective trait dimensions will each explain a unique amount of variance in social cognitive performance.